Knock! Knock! How does knowledge management maintain organizational performance in organization? A systematic literature review - Putu Gde Arie Yudhistira; I Gede Riana; I Wayan Supartha; I Made Artha Wibawa (Global Business & Finance Review (GBFR), 2024)
Purpose: The aim was to better understand Knowledge Management in organizations by a systematic literature review. Design/methodology/approach: The present review followed the guidelines of PRISMA and conducted a thematic analysis. It encompassed a comprehensive examination of 24 articles obtained from Scopus, Emerald, and Science Direct databases. Findings: Based on thematic analysis, this review identifies that knowledge management plays a crucial role in maintaining organizational performance. Through practices such as capturing, storing and sharing relevant knowl-edge, organizations can improve operational efficiency, innovation and responsiveness to the external environment. In addition, knowledge management also facilitates continuous organizational learning, enabling organizations to adapt to market changes and create added value for stakeholders. Research limitations/implications: The recent study was limited to empirical research based on three databases and only for research conducted on knowledge management in organizations. These findings are expected to direct future research to ensure the theoretical framework in knowledge management research and have an outlook on influencing resources. Originality/value: This study has successfully identified the theoretical foundation and resources that affect knowl-edge management performance. The theoretical foundation for the research is divided into RBV, KBV, and DCV which frame the reviewed study.
Keywords: 650; Knowledge Management; Organizational Performance; Human Resource Management; Organizational Management; Resource Based View; Knowledge Based View